Pelaksanaan Pemancangan Pondasi Tiang Pancang Menggunakan Hydraulic Static Pile Driver pada Proyek Pembangunan Gedung Pringgodigdo Universitas Airlangga Surabaya - Aisyatur Rahmah (Jurnal Vokasi Teknik Sipil, 2024)
Project activity is an activity that requires careful planning so that its implementation runs smoothly. One of them is a construction development project. Therefore, researchers are interested in discussing construction development. This study aims to examine and analyze related piling work, namely starting from the piles used, the piling tools used, to the stages in the piling work. This type of research is quantitative research. The data collection techniques used in this research are observation, interviews, literature, working drawings from the project and documentation. The piling method uses a compressive mode so that the piles reach the depth of the soil. The informants of this research are people who are in the Pringgodigdo Building Construction project, Airlangga University Surabaya right on Jl. Dharmawangsa No. 4-6, Kec. Gubeng, Surabaya. The results of this study indicate that in the construction of the Pringgodigdo Building, piling work was carried out using a diameter 60 spun pile using a ZYJ type HSPD (Hydraulic Static Pile Driver) piling tool.46 The results of the calculation of HSPD machine productivity are in line with the specifications